2014
DOI: 10.18845/tm.v27i1.1693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de posibles medidas para reducir las emisiones de fuentes móviles en Costa Rica, 2010-2015

Abstract: <p>Se evaluó el impacto de las posibles medidas para reducir las emisiones generadas por fuentes móviles en Costa Rica para ser ejecutadas en el periodo 2010-2015. La estimación de las emisiones se realizó utilizando los factores de emisión obteni­dos del modelo Mobile 6 y los datos de actividad distribuidos por tipo de vehículo y combustible. El estudio determinó que la sustitución del 50% de las unidades de transporte público por vehículos más eficientes resulta ser la medida más eficaz para contrarres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These delivery practices, which also take place in medium size companies, have impacts that need to be further studied because even though the territory is small, the country endures today high levels of occupation in the central plateau, which are causing high congestion in road transportation. Herrera-Murillo et al (2014) [23] found that the vehicle fleet increased uninterruptedly at an annual rate of 13.3% during the period of 2001-2009 and continues with a similar tendency. Private transit has been growing at an annual rate of 8%, however the road infrastructure has not been upgraded at the same rate, given rise to saturation.…”
Section: Transportation Infrastructure Characterizationmentioning
confidence: 96%
See 2 more Smart Citations
“…These delivery practices, which also take place in medium size companies, have impacts that need to be further studied because even though the territory is small, the country endures today high levels of occupation in the central plateau, which are causing high congestion in road transportation. Herrera-Murillo et al (2014) [23] found that the vehicle fleet increased uninterruptedly at an annual rate of 13.3% during the period of 2001-2009 and continues with a similar tendency. Private transit has been growing at an annual rate of 8%, however the road infrastructure has not been upgraded at the same rate, given rise to saturation.…”
Section: Transportation Infrastructure Characterizationmentioning
confidence: 96%
“…They indicate that 45% of the vehicles from years 1993 and older emit 62% of the reactive organic gases and 42% of the nitrogen oxides. Herrera-Murillo et al (2014) [23] concluded that transport vehicles are the main sources of air pollution especially in urban zones, where 28.1% of the units that use diesel as a fuel are years 1993 or older, thus lacking means for emissions control.…”
Section: Transportation Infrastructure Characterizationmentioning
confidence: 99%
See 1 more Smart Citation